Digital Media Exposure and Predictors for Screen Time in 12-Month-Old Children: A Cross-Sectional Analysis of Data From a German Birth Cohort - Durham, Kira; Wethmar, David; Brandstetter, Susanne; Seelbach-Göbel, Birgit; Apfelbacher, Christian; Melter, Michael; Kabesch, Michael; Kerzel, Sebastian; , The KUNO Kids Study Group; Ambrosch, Andreas; Arndt, Petra; Baessler, Andrea; et al. (Frontiers in Psychiatry, 2021)
Background: Early exposure to digital media may affect the physical and cognitive development in young children. The American Academy of Pediatrics and national guidelines recommend no digital media use at all under the age of 18 months. The aim of our study was to determine the actual exposure to digital media in 12-month-old infants and to reveal potential risk factors for screen time. Methods: In this prospective cross-sectional survey, data was collected from the KUNO Kids birth cohort study using parent-report questionnaires regarding the media exposure of the study child. We determined age at first contact with different digital media, mean screen time on an average weekday, and the influence of major demographic and socioeconomic factors. Results: Data for screen time analysis was available for 630 children. In summary, 45 % of children had already been exposed to digital media by their first birthday. The most frequent first digital media exposure was the TV (33.0 %) followed by smartphones (16.9 %), both most commonly exposed to around the age of 8 months. On a regular weekday, 20 % of the children spent 0.5-1 h in front of a TV and 9 % were exposed to a smartphone for the same time frame, compared to 31 % of joint parent-child media use. Predictors for screen time were having a sibling, less living space per person, and excessive TV use in the household, the latter of which doubled the chance of the child being exposed to digital media. Conclusion: A proportion of 10 % of 1-year-old children were already regularly exposed to digital media. The TV remains the most predominant device but new media, particularly smartphones, might be catching up. Our study provides further support that family TV time is a major predictor of infant screen time. Pediatric recommendations should be re-evaluated in the light of the actual exposure to digital media already in infancy and parents should be proactively counseled regarding possible effects on child development.